Combined frequency-tagging EEG and eye tracking reveal reduced social bias in boys with autism spectrum disorder. (April 2020) - Vettori, Sofie; Dzhelyova, Milena; Van der Donck, Stephanie; Jacques, Corentin; Van Wesemael, Tim; Steyaert, Jean; Rossion, Bruno; Boets, Bart
Abstract: Developmental accounts of autism spectrum disorder (ASD) state that infants and children with ASD are spontaneously less attracted by and less proficient in processing social stimuli such as faces. This is hypothesized to partly underlie social communication difficulties in ASD. While in some studies a reduced preference for social stimuli has been shown in individuals with ASD, effect sizes are moderate and vary across studies, stimuli, and designs. Eye tracking, often the methodology of choice to study social preference, conveys information about overt orienting processes but conceals covert attention, possibly resulting in an underestimation of the effects. In this study, we recorded eye tracking and electroencephalography (EEG) during fast periodic visual stimulation to address this issue. We tested 21 boys with ASD (8-12 years old) and 21 typically developing (TD) control boys, matched for age and IQ. Streams of variable images of faces were presented at 6 Hz alongside images of houses presented at 7.5 Hz or vice versa, while children were engaged in an orthogonal task. While frequency-tagged neural responses were larger in response to faces than simultaneously presented houses in both groups, this effect was much larger in TD boys than in boys with ASD. This group difference in saliency of social versus non-social processing is significant after 5 sec of stimulus presentation and holds throughout the entire trial. Although there was no interaction between group and stimulus category for simultaneously recorded eye-tracking data, eye tracking and EEG measures were strongly correlated. We conclude that frequency-tagging EEG, allowing monitoring of both overt and covert processes, provides a fast, objective and reliable measure of decreased preference for social information in ASD.